46.5k views
4 votes
What's the tenth term of a sequence with an explicit rule of ƒ(n) = 2 + (–3)(n – 1)? A) ƒ(10) = –25B) ƒ(10) = 27C) ƒ(10) = –30D) ƒ(10) = 32

User Zihado
by
5.1k points

1 Answer

1 vote

The nth term of a sequence is given as

f(n) = 2 + (-3)(n-1)

To find the 10th term, Let n = 10

Substitute the value of n= 10 into the expression

f(10) = 2 + (-3) (10 - 1)

f(10) = 2 + (-3) (9)

f(10) = 2 + (-27)

F(10) = 2 - 27

f(10) = -25

The answer is -25

User Ahmethungari
by
5.0k points